Extending social accountability mandates to biomedical research in Canadian faculties of medicine - Wiper-Bergeron, Nadine; Adam, Holly L; Eady, Kaylee; Moreau, Katherine A; Kennedy, Christopher RJ; Kendall, Claire E (Canadian Medical Education Journal, 2024)
Background: Social accountability (SA), as defined by Boelen and Heck, is the obligation of medical schools to address the needs of communities through education, research and service activities. While SA is embedded within health profession education frameworks in medicine, they are rarely taught within graduate-level (MSc/PhD) education. Methods: As these programs train future medical researchers, we invited first-year graduate students enrolled in a mandatory professionalism class at our institution (n = 111) to complete a survey on their perceptions of the importance of SA in their research, training, and future careers. Results: Over 80% (n = 87) of respondents agreed that SA is relevant and felt committed to integrating it into their future research activities, only a limited number of students felt confident and/or supported in their abilities to integrate SA into their research. Conclusions: Specific SA training in graduate education is necessary for students to effectively incorporate elements of SA into their research, and as such support the SA mandates of their training institutions. We posit that awareness of SA principles formalizes the professional standards for biomedical researchers and is thus foundational for developing a professionalism curriculum in graduate education programs in medicine. We propose an expansion of the World Health Organization (WHO) partnership pentagon to include partners within the research ecosystem (funding partners, certification bodies) that collaborate with biomedical researchers to make research socially accountable.